Online Interprofessional Education and Practice for Health Care Professionals Improves Substance Use Treatment Capacity - Parry, Nicola (MD Conference Express, 2015)
Substance abuse represents an enormous public health problem, and its comorbidity with mental disorders is well recognized. However, many people need specialty treatment for substance abuse problems but do not receive it. This article reviews results from an online interprofessional project demonstrating the effectiveness of interprofessional collaborative practice and its impact on substance use health care in rural areas.